Blastic transformation of p53-deficient bone marrow cells by p210(bcr/abl) tyrosine kinase - Skorski, Tomasz (The National Academy of Sciences of the USA, 1996)
Blastic transformation of chronic myelogenous leukemia (CML) is characterized by the presence of nonrandom, secondary genetic abnormalities in the majority of Philadelphia(1) clones, and loss of p53 tumor suppressor gene function is a consistent finding in 25–30% of CML blast crisis patients. To test whether the functional loss of p53 plays a direct role in the transition of chronic phase to blast crisis, bone marrow cells from p53(+/+) or p53(−/−) mice were infected with a retrovirus carrying either the wild-type BCR/ABL or the inactive kinase-deficient mutant, and were assessed for colony-forming ability. Infection of p53(−/−) marrow cells with wild-type BCR/ABL, but not with the kinase-deficient mutant, enhanced formation of hematopoietic colonies and induced growth factor independence at high frequency, as compared with p53(+/+) marrow cells. These effects were suppressed when p53(−/−) marrow cells were coinfected with BCR/ABL and wild-type p53. p53-deficient BCR/ABL-infected marrow cells had a proliferative advantage, as reflected by an increase in the fraction of S+G(2) phase cells and a decrease in the number of apoptotic cells. Immunophenotyping and morphological analysis revealed that BCR/ABL-positive p53(−/−) cells were much less differentiated than their BCR/ABL-positive p53(+/+) counterparts. Injection of immunodeficient mice with BCR/ABL-positive p53(−/−) cells produced a transplantable, highly aggressive, poorly differentiated acute myelogenous leukemia. In marked contrast, the disease process in mice injected with BCR/ABL-positive p53(+/+) marrow cells was characterized by cell infiltrates with a more differentiated phenotype and was significantly retarded, as indicated by a much longer survival of leukemic mice. Together, these findings directly demonstrate that loss of p53 function plays an important role in blast transformation in CML.